Khalwat melalui Chatting dan Video Call: Studi Takhrij dan Syarah Hadis - Nurhusna Rahma Dina; Muhamad Yoga Firdaus; Taufik Rahman (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith syarah about seclusion regarding the phenomenon of Chatting and Video Calls. This research uses qualitative research through literature study and analysis. This study uses two methods to collect data, namely takhrij and syarah hadith. This study resulted that the quality status of the hadith about seclusion, namely, shahih li dzatihi, both in terms of sanad and matan, and this hadith is acceptable (maqbul) and can be practiced. The conclusion of this study is that technological developments cause the emergence of social interaction through online social media such as chat and Video Calls that are not in accordance with Islamic law, which is a form of seclusion that can lead to adultery, this has been prohibited by the Prophet Muhammad, therefore the law of this interaction is haram unless the interaction is in accordance with Islamic law.